Emission control of entangled electrons in photoionisation of a hydrogen molecule - Shobeiry, Farshad; Froß, Patrick; Srinivas, Hemkumar; Pfeifer, Thomas; Moshammer, Robert; Harth, Anne (Scientific reports, 2024)
For photo-dissociation of a single hydrogen molecule ($$H_2$$) with combined XUV and IR laser pulses, we demonstrate optical control of the emission direction of the photoelectron with respect to the outgoing neutral fragment (the H-atom). Depending on the relative delay between the two laser fields, adjustable with sub-femtosecond time resolution, the photoelectron is emitted into the same hemisphere as the H-atom or opposite. This emission asymmetry is a result of entanglement of the two-electron final-state involving the spatially separated bound and emitted electron.
Gesehen am 17.02.2025